High functional allelic diversity and copy number in both MHC classes in the common buzzard - Jamie Winternitz; Nayden Chakarov; Tony Rinaud; Meinolf Ottensmann; Oliver Krüger (BMC Ecology and Evolution, 2023)
Abstract Background The major histocompatibility complex (MHC), which encodes molecules that recognize various pathogens and parasites and initiates the adaptive immune response in vertebrates, is renowned for its exceptional polymorphism and is a model of adaptive gene evolution. In birds, the number of MHC genes and sequence diversity varies greatly among taxa, believed due to evolutionary history and differential selection pressures. Earlier characterization studies and recent comparative studies suggest that non-passerine species have relatively few MHC gene copies compared to passerines. Additionally, comparative studies that have looked at partial MHC sequences have speculated that non-passerines have opposite patterns of selection on MHC class I (MHC-I) and class II (MHC-II) loci than passerines: namely, greater sequence diversity and signals of selection on MHC-II than MHC-I. However, new sequencing technology is revealing much greater MHC variation than previously expected while also facilitating full sequence variant detection directly from genomic data. Our study aims to take advantage of high-throughput sequencing methods to fully characterize both classes and domains of MHC of a non-passerine bird of prey, the common buzzard (Buteo buteo), to test predictions of MHC variation and differential selection on MHC classes. Results Using genetic, genomic, and transcriptomic high-throughput sequencing data, we established common buzzards have at least three loci that produce functional alleles at both MHC classes. In total, we characterize 91 alleles from 113 common buzzard chicks for MHC-I exon 3 and 41 alleles from 125 chicks for MHC-IIB exon 2. Among these alleles, we found greater sequence polymorphism and stronger diversifying selection at MHC-IIB exon 2 than MHC-I exon 3, suggesting differential selection pressures on MHC classes. However, upon further investigation of the entire peptide-binding groove by including genomic data from MHC-I exon 2 and MHC-IIA exon 2, this turned out to be false. MHC-I exon 2 was as polymorphic as MHC-IIB exon 2 and MHC-IIA exon 2 was essentially invariant. Thus, comparisons between MHC-I and MHC-II that included both domains of the peptide-binding groove showed no differences in polymorphism nor diversifying selection between the classes. Nevertheless, selection analysis indicates balancing selection has been acting on common buzzard MHC and phylogenetic inference revealed that trans-species polymorphism is present between common buzzards and species separated for over 33 million years for class I and class II. Conclusions We characterize and confirm the functionality of unexpectedly high copy number and allelic diversity in both MHC classes of a bird of prey. While balancing selection is acting on both classes, there is no evidence of differential selection pressure on MHC classes in common buzzards and this result may hold more generally once more data for understudied MHC exons becomes available.